Golf tips from the stars - Elliott, Bill; Platts, Mitchell; Trevillion, Paul (Stanley Paul, 1993)
One of the special attractions of the great game of goft is that the world's top players face the same challenges as the weekend amateur. The problems confronted from tee to green, whether they are an ailing swing or a disobedient putting stroke, confidence or club selection, manifest themselves in monthly medals just as they do in major championships.